The Correlation Between Physical Composition and Smash Proficiency in Badminton Players at MAN Pangkep - Burhan, Ahmad Syarif; Hamzah, Fajri; Sihombing, Binsar Hasudungan (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. To ascertain the association between physical structure and smashing capability. sports. This research is a qualitative descriptive study. Materials and Methods. The study population comprised all MAN students. Pangkep possesses 47 badminton players. The sample for this study comprised 30 participants selected by the Simple Random Sampling methodology utilizing the lottery method. Results. A substantial correlation exists between multiple physical variables and smash capability in badminton. The criteria encompass height, arm length, leg length, chest circumference, thigh circumference, and weight. All of these criteria substantially influence a player's capacity to execute a successful smash. Conclusion. This study concludes that there is a significant relationship between body structure (height, arm length, leg length, chest circumference, thigh circumference, and body weight) with smash ability in MAN Pangkep badminton players. Good body structure contributes positively to the effectiveness of smash strokes.